La importancia de los estudios de adopción e impacto: el caso del proyecto integrado de yuca en la costa norte de Colombia - Gottret, María Verónica; Henry, Guy (International Center for Tropical Agriculture, 1994)
Adoption and impact studies have been designed to determine the returns to resources invested in research. They are important as a tool for focusing R&D activities and as a mechanism for ex ante and ex post feedback. The document is divided into four parts: the first reviews recent adoption and impact studies and the mechanisms for their evaluation. The second presents a case study on the adoption and impact of technologies within the Integrated Cassava Project, carried out by DRI (the Colombian Fund for Integrated Rural Development) and the CIAT Cassava Program in a region of Colombia, known as the North Coast. The third part discusses the results as related to previous terms of reference, and the fourth part gives recommendations on how to design evaluations of research programs. Between 1984 and 1991, small-farmer cooperatives, who participated in the Integrated Cassava Project in the North Coast, adopted cassava-drying technologies and created new markets that established a base price, which favored increased planting of cassava and benefitted, not only urban consumers of fresh cassava, but also buyers of dried cassava, processors, intermediaries, and producers. In 1991, the region had 142 drying plants producing 25,000 MT to meet a demand of 62,000 MT of fresh roots. During this same period, the area planted to cassava increased from 55,000 ha to 110,337 ha. Factors that influence the adoption of drying technology are distance to market centers, access to credit and technical assistance, relative importance of cassava as agricultural crop, and the formation of cassava growers` associations.